DOES THE SOCIAL NETWORK RELATE WITH THE ENTREPRENEURSHIP? AN EMPIRICAL CONTENT ANALYSIS - Arissetyanto Nugroho; Janfry Sihite (Jurnal Manajemen., 2015)
The aim of the content analysis is to construct social network terminology inentrepreneurship journal. There are 97 journal abstracts that analyzed from six keyword search query in Proquest, the queries are “Entrepreneur & Behavior”, “Entrepreneurship & Creativity & Innovation”, “Entrepreneurship & Social Network”, “Entrepreneurship & Culture”, “Entrepreneurship & Marketing” and “Global Entrepreneurship Monitor”. All the abstracts analyzed with Provalis Research QDA Miner, a Qualitative Quantitative Data Analysis software. QDA miner identified relevant keyword, relate keywords with jaggard coefficient of cooccurrence and the proximity plot. All the relevant keywords being analyzed with Multidimensional Scaling (MDS) and construct the relevant keywords regards to social network. Finally, there are two main findings, the first findingdistinquishes the three level of analysis framework which are the individual level, the firm level and the macro level as representation of the continuous process to accumulate resources. The second finding construct social network as national culture, furthermore the construct of social network closely related with social capital and human capital.